Implementation Technique Breast-feed With Nipples Milk Scratches On Mother Baby At Rs Viqueque City Regency Dili Timor Leste - Erma Retnaningtyas; Florentina Da Costa; S. Tauriana (Master of Public Health Program Universitas STRADA Indonesia, 2024)
According to Soetjiningsih (1997), the most common problem in breastfeeding is nipple pain / blisters, about 57% of mothers who breastfeed reported having suffered from blisters on their nipples. Nipples of blisters can prevent exclusive breastfeeding. Based on data in the Viqueque district hospital in Dili East Timor 2019, in 10 breastfeeding mothers, there were still many breastfeeding mothers who experienced blisters on the nipples . The design of this study included quantitative research with cross-sectional type of correlation design. The population in this study were all breastfeeding mothers who visited the Viqueque City Hospital in East Timor by taking the sample with the type of accidental sampling, amounting to 44 respondents. The variable in this research is the technique of breastfeeding and nipple milk with ordinal scale. This research was conducted in December 2019 until July 2020. In this study analyzed by contingency coefficient test with α o, 05. The results of the study after being tested with contingency coefficient obtained p-value = 0.008 < α = 0.05 (p-value <α) which means that H0 is rejected and H1 is accepted, which means that there is a relationship between breastfeeding techniques and nipple milk nipples. Incorrect position in breastfeeding is a natural thing that occurs early in the breastfeeding period. Both mother and baby are in the learning stage. If the position is improperly attempted, the position is replaced until finally I find the right position. As time goes by, mother will become professional until finally she can find the right position for mother and baby. When the position is right, surely the mother's nipples will not blister.